Adherence to severe malaria treatment guidelines in Northern Uganda: a mixed-methods study - Zainab Akello; Joseph Oloro; Marie Francoise Mukanyangezi; Domina Asingizwe (Malaria Journal, 2025)
Background Adherence to severe malaria treatment guidelines is crucial for effective case management and reducing malaria-related morbidity and mortality. However, non-compliance among healthcare workers remains a challenge, particularly in resource-limited settings. This study assessed the level of adherence to severe malaria treatment guidelines among healthcare workers in public hospitals in the Acholi sub-region of Northern Uganda and explored factors influencing this adherence. Methods A convergent parallel mixed-methods design was employed, incorporating both quantitative and qualitative approaches. Quantitatively, 384 patient records from Anaka General Hospital, Kitgum General Hospital, and Gulu Regional Referral Hospital were reviewed using a checklist. Qualitative data were collected via key informant interviews (KIIs) among nine purposely selected Healthcare Workers. Descriptive statistics were used to summarize adherence levels, and a modified Poisson regression analysis was conducted to identify associated factors. Statistical significance was set at p<0.05. Thematic analysis using NVivo software was done for the qualitative part. Results The level of adherence to severe malaria treatment guidelines was 33.07%. Non-adherence was observed for recommended treatment with intravenous (IV) drugs followed by oral medications for severe malaria (38.3%) and treatment of only malaria confirmed (25%). Medical doctors were more likely to adhere to malaria treatment guidelines [aIRR1.7, p=0.035] than other professionals. The qualitative findings categorized the facilitators of adherence into four themes including healthcare workers’ knowledge and training support, institutional and policy support, guidelines accessibility and ease use, healthcare workers’ positive attitudes and motivation. Barriers to adherence included knowledge and awareness gaps, resource availability constraints, as well as socio-cultural and patient factors. Conclusion Adherence to severe malaria treatment guidelines in Uganda is suboptimal, with significant gaps in prescribing practices. Institutionalization of routine refresher training, mentorship and support supervision for healthcare workers are critical to achieving Uganda’s 2025 malaria reduction targets
Keywords: Severe malaria; Malaria treatment guidelines; Adherence; Uganda